2010
DOI: 10.1002/app.33186
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and initiation polymerization mechanism of α‐methylstyrene‐containing macroinitiators

Abstract: Copolymers obtained from radical copolymerization of a-methylstyrene (AMS) and glycidyl methacrylate (GMA) behave as macroinitiators, when heated in the presence of a second monomer, giving rise to block copolymers. The relevant degradation and initiation polymerization mechanism of the macroinitiators were studied. Thermal depropagation of the macroinitiators generated monomers, identified by 1 H-NMR, photoionization mass spectroscopy and FT-IR. According to the results of structure analysis by GPC, ESR and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…However, it is easy to carry out radical copolymerization using other monomers and to thus form a high molecular weight copolymer. AMS copolymers easily decompose and produce chain radicals after being heated to approximately 90 °C; thus, they can be used as macroinitiators to prepare graft and block copolymers . Glycidyl methacrylate (GMA) has been widely used in the modification of polyolefin because of its characteristics of nontoxicity and high activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is easy to carry out radical copolymerization using other monomers and to thus form a high molecular weight copolymer. AMS copolymers easily decompose and produce chain radicals after being heated to approximately 90 °C; thus, they can be used as macroinitiators to prepare graft and block copolymers . Glycidyl methacrylate (GMA) has been widely used in the modification of polyolefin because of its characteristics of nontoxicity and high activity .…”
Section: Introductionmentioning
confidence: 99%
“…AMS copolymers easily decompose and produce chain radicals after being heated to approximately 90 8C; thus, they can be used as macroinitiators to prepare graft and block copolymers. 12,13 Glycidyl methacrylate (GMA) has been widely used in the modification of polyolefin because of its characteristics of nontoxicity and high activity. [14][15][16] Tetraphenylethylene can emit strong light in a solid state as a typical aggregation-induced emission (AIE) effect, and this can be used in fluorescence labeling.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the fact of the molecular weights of the polymers increased significantly with the monomer conversions, it might be concluded that there might be polymer chains keeping active during the St polymerization initiated by PAS macroinitiator. In previous reports, it was demonstrated that weak bonds in AMS copolymer macroinitiators, such as ‐AMS‐AMS‐ (head–head) and ‐AMS‐M‐ (head–head), could give the birth of new chain radicals when heated . In the polymerization of St, the AMS‐containing weak bonds (as illustrated in Scheme ) in PAS macroinitiator could generate chain radicals to initiate the polymerization at the reaction temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, when monomer concentration decreased at the latter stage of the polymerization, the effects of degradation of AMS units got strong. The degradation of AMS‐containing copolymer might cause the decrease of the molecular weight at high temperature . As a result, there were AMS‐containing oligomers in the resulting products, which would also cause the existence of the peaks at low molecular weight in the GPC traces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation